2004
DOI: 10.1001/jama.292.21.2600
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Neoplasia, Autoimmune Thyroiditis, and Hypothyroidism in Persons Exposed to Iodine 131 From the Hanford Nuclear Site

Abstract: Context Approximately 740000 Ci (2.73 ϫ 10 16 Bq) of iodine 131 (131 I) were released to the atmosphere from the Hanford Nuclear Site in Washington State from 1944 through 1957. The risk of thyroid disease resulting from prolonged environmental 131 I exposure is poorly understood. Objective The Hanford Thyroid Disease Study (HTDS) was conducted to determine if thyroid disease is increased among persons exposed as children to atmospheric releases of 131 I from Hanford. Design Retrospective cohort study. Exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
76
2
3

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 64 publications
10
76
2
3
Order By: Relevance
“…This is lower than an excess relative risk of 13.0 per gray (95 percent CI: 2.7, 68.7; n ¼ 20) from the Nevada test site study (29) and much higher than 0.1 per gray (95 percent CI: <À0.3, 2.2; n ¼ 33) from the Hanford Thyroid Disease Study (27). Davis et al (27) have suggested that some of the differences in estimates lie in the different composition of the radionuclides in the fallout: While the Hanford Thyroid Disease Study thyroid dose was mostly due to 131 I, other radionuclides as well as external ionizing radiation exposures had greater contribution in the doses analyzed in the Nevada test site study. Hoffman et al (43) suggested that high uncertainties in dose reconstructions in the Hanford Thyroid Disease Study may account for negative findings.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…This is lower than an excess relative risk of 13.0 per gray (95 percent CI: 2.7, 68.7; n ¼ 20) from the Nevada test site study (29) and much higher than 0.1 per gray (95 percent CI: <À0.3, 2.2; n ¼ 33) from the Hanford Thyroid Disease Study (27). Davis et al (27) have suggested that some of the differences in estimates lie in the different composition of the radionuclides in the fallout: While the Hanford Thyroid Disease Study thyroid dose was mostly due to 131 I, other radionuclides as well as external ionizing radiation exposures had greater contribution in the doses analyzed in the Nevada test site study. Hoffman et al (43) suggested that high uncertainties in dose reconstructions in the Hanford Thyroid Disease Study may account for negative findings.…”
Section: Discussionmentioning
confidence: 74%
“…However, no thyroid doses were available for analysis. The other two, one investigating the effects of the fallout after nuclear weapons testing at the Nevada test site (29) and the other (the Hanford Thyroid Disease Study) (27) investigating the effects of atmospheric releases, relied on dose reconstructions based on residential history years after exposures had occurred, and they were based on small numbers of cases of ''thyroid neoplasia.'' Our risk estimate for ''thyroid neoplasia'' was 4.39 per gray (95 percent CI: 1.67, 13.28; n ¼ 58 cases).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Most medical exposures to 131 I have occurred in adults, who are relatively insensitive to radiationrelated thyroid carcinogenesis based on data from populations exposed to external radiation (4). (3) Environmental exposures of children to radioiodines have occurred, notably from the 1986 reactor accident at Chernobyl (7), atmospheric releases from the Hanford Nuclear Site in Washington state (43)(44)(45), and fallout from nuclear tests in the Marshall Islands in the Central Pacific (46), the Nevada Test Site in the U.S. (3,(47)(48)(49), as well as the SNTS (11,25). However, studying such exposed populations can pose enormous problems in individual dose reconstruction and case identification.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 On the other hand, smaller amounts of radiation exposure, i.e. from either lower dosage of fallout 37 or from diagnostic use of radioisotopes, have not been associated with a higher incidence of thyroid cancer. Thus, diagnostic 131-Iodine was not associated with thyroid neoplasia in a total of over 6000 children 38,39 or in another review of 2727 patients who received 131-Iodine therapy for hyperthyroidism.…”
Section: Additional Factorsmentioning
confidence: 99%